Satisfaction study towards classroom language training courses of English teachers in primary educational service area office, Nakhon Pathom province, Thailand - WANNEE NIAMHOM; SUNTI SRISUANTANG; PRASONG TANPICHAI (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: This study aims to investigate and compare English teachers’ levels of contentment with their participation in language training courses offered by the Primary Educational Service Area Office in Nakhon Pathom Province, Thailand. This research aimed to compare English teachers’ satisfaction levels with classroom language training courses in the Primary Educational Service Area Office in Nakhon Pathom Province based on demographic variables such as gender, years of experience as educators, and student population size.Method: Nakhon Pathom’s Primary Educational Service Area Office enlisted the help of 28 English teachers for their research. A questionnaire served as the data collection tool for this study. Frequency, percentage, mean, standard deviation, t-test, and one-way analysis of variance were used to analyse the data.Findings: The following are the study results: (1)English instructors rated their classroom language training courses as excellent or very good in all categories, except for the facilities used to support the training courses, which they rated as moderate. (2) Examining the attitudes of English instructors toward their own classroom language-learning programmes.Implications/Novel Contribution: This research is crucial because it contributes significantly to the body of literature on language instruction and provides helpful guidelines for students and instructors.